Cation‐Specific Electrokinetic Separations Using Prussian Blue Intercalation Reactions. Issue 19 (14th October 2020) - Thompson, Jonathan R.; Davies, Collin D.; Clausmeyer, Jan; Crooks, Richard M.
Abstract: We report a new approach for forming ion depletion zones (IDZs) using intercalation reactions at an electrochemically controlled Prussian blue (PB) film. The experiments described here were performed using a microfluidic device, wherein a charged fluorophore in solution was used as a proxy to monitor IDZ formation. In the presence of K +, intercalation reactions proceed readily to form an IDZ, and thus enrich the fluorophore up to 37‐fold. In the presence of the larger hydrated Li + or tetrabutylammonium (TBA + ) ions, however, ion intercalation proceeded less quickly than with K + . Slower ion intercalation resulted in a weaker IDZ and correspondingly lower enrichment factors of eight‐ and six‐fold, respectively. These results are significant because they show that PB intercalation reactions selectively form an IDZ. Accordingly, we anticipate that these findings will lead to a better understanding and further interesting applications of intercalation materials like PB for efficient and selective enrichment and separations. Abstract : Separate to accumulate : Prussian blue intercalation reactions are shown to selectively form an ion depletion zone and accompanying electric field gradient. Experiments and numerical simulations demonstrate how this electric field gradient is useful for enriching ions.